PEMANFAATAN ARTIFICIAL INTELLIGENCE OLEH GURU DALAM MENYUSUN BAHAN AJAR PADA KURIKULUM MERDEKA DI SD NEGERI 115 PEKANBARU - Rizqo Alfi; Siti Quratul Ain (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The rapid advancement of Artificial Intelligence (AI) has opened new opportunities for teachers to develop teaching materials more efficiently and creatively, particularly within the implementation of the Merdeka Curriculum. This study aimed to describe AI utilization by teachers in developing teaching materials, identify influencing factors, and analyze its implications for teachers' pedagogical practices. A descriptive qualitative approach was employed, with three teachers at SD Negeri 115 Pekanbaru selected as subjects through purposive sampling. Data were collected through observation, interviews, and documentation, then analyzed via data reduction, data display, and conclusion drawing. Data validity was ensured through technique triangulation. Findings revealed that all three teachers actively and systematically used AI through various platforms including ChatGPT, Gemini, Claude, Canva, Gamma, Padlet TA, and Grok. while consistently filtering and verifying outputs to align with the established Learning Outcomes and Learning Objectives. AI utilization was influenced by internal factors such as motivation and positive perceptions, and external factors including school-provided facilities and technical training programs. Pedagogically, AI enhanced time efficiency and instructional variety, yet decision-making authority remained fully in the hands of teachers. This study concludes that AI utilization at this school has progressed toward mature pedagogical integration, transcending mere technical adoption.